MODELING OF BLOOD FLOW PARAMETERS (VELOCITY AND PRESSURE) DEPENDING ON BLOOD VESSEL GEOMETRIC PATTERN - D. A. Baliuk; I. Y. Bazik; E. D. Vitkouski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main human carotid artery pathologic patterns are considered. The results of artificial finite elements method modelling of blood flow via FlowVision software package are shown in various pathologic patterns of carotid arteries.